1978
DOI: 10.1073/pnas.75.6.2732
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of translation by poliovirus: inactivation of a specific initiation factor.

Abstract: Translation of vesicular stomatitis virus (VSV) mRNA, like host mRNA translation, is inhibited in cells infected with poliovirus. To study the mechanism of poliovirus-induced inhibition of protein synthesis, we prepared extracts from poliovirus-infected and uninfected HeLa cells. Poliovirus mRNA was translated in Iysates from both infected and uninfected cells, while VSV mRNA was translated only in the lysate from uninfected cells. Addition of purified translation initiation factors to the extract frosi infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
122
2
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(131 citation statements)
references
References 30 publications
6
122
2
1
Order By: Relevance
“…It has been suggested that poliovirus infection leads to the specific inactivation of an initiation factor required for the translation of capped mRNAs (Helentjaris & Ehrenfeld, 1978;Rose et al, 1978;Trachsel et al, 1980). In agreement with this suggestion, poliovirus infection of HeLa cells interferes with the development of herpesvirus and leads to the inhibition of vesicular stomatitis virus (VSV) protein synthesis under some conditions (Doyle & Holland, 1972;Saxton & Stevens, 1972;Ehrenfeld &Lund, 1977).…”
Section: Introductionsupporting
confidence: 48%
See 1 more Smart Citation
“…It has been suggested that poliovirus infection leads to the specific inactivation of an initiation factor required for the translation of capped mRNAs (Helentjaris & Ehrenfeld, 1978;Rose et al, 1978;Trachsel et al, 1980). In agreement with this suggestion, poliovirus infection of HeLa cells interferes with the development of herpesvirus and leads to the inhibition of vesicular stomatitis virus (VSV) protein synthesis under some conditions (Doyle & Holland, 1972;Saxton & Stevens, 1972;Ehrenfeld &Lund, 1977).…”
Section: Introductionsupporting
confidence: 48%
“…On the basis that cell-free systems from poliovirus-infected cells translate uncapped mRNAs but not capped mRNAs (Rose et al, 1978;Trachsel et al, 1980), it was suggested that poliovirus infection inactivates a protein factor necessary for the translation of capped mRNAs, but dispensable for the translation of uncapped mRNAs. In agreement with this idea, infection of cells with poliovirus interferes with the translation of herpesvirus or VSV mRNAs (Doyle & Holland, 1972;Saxton & Stevens, 1972;Ehrenfeld &Lund, 1977).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, not all reovirus proteins behave in the same way, because some of them are more resistant to inhibition than others. This result is difficult to explain if we assume that poliovirus destroys a factor involved in cap recognition, necessary for the translation of capped reovirus m R N A s (Rose et al, 1978). The pattern of translation after EMC virus superinfection was similar, i.e.…”
Section: Protein Synthesis In Hela Cells Infected With Reovirus and Smentioning
confidence: 73%
“…Poliovirus and EMC virus inhibit host protein synthesis in HeLa cells to different degrees, so that higher multiplicities of EMC virus than poliovirus are required to inhibit protein synthesis in HeLa cells with similar kinetics. Because of this difference in inhibition of host protein synthesis between EMC virus and poliovirus, and because of the different ability of the extracts from EMC virus-and poliovirus-infected cells to translate capped mRNAs (Lawrence & Thach, 1974;Rose et al, 1978), Jen et al (1980) suggested that the mechanisms used by both viruses to block host protein synthesis are different.…”
Section: Introductionmentioning
confidence: 99%